2013
DOI: 10.1103/physreve.87.063106
|View full text |Cite
|
Sign up to set email alerts
|

Local and nonlocal anisotropic transport in reversed shear magnetic fields: Shearless Cantori and nondiffusive transport

Abstract: A study of anisotropic heat transport in reversed shear (nonmonotonic q-profile) magnetic fields is presented. The approach is based on a recently proposed Lagrangian-Green's function method that allows an efficient and accurate integration of the parallel (i.e., along the magnetic field) heat transport equation. The magnetic field lines are described by a nontwist Hamiltonian system, known to exhibit separatrix reconnection and robust shearless (dq/dr=0) transport barriers. The changes in the magnetic field t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…[16]. More recently, the role of Cantori on anisotropic heat transport in plasmas has been studied in the context of steady state solutions [17] and time dependent solutions in monotonic and reversed shear magnetic configurations [3,4]. The basic idea is that although invariant closed curves (which correspond to flux surfaces in the Hamiltonian description of magnetic fields) present impenetrable transport barriers, regions without such curves (e.g., the region around R 2 ψ ≈ 0.275 in (1/2πL) L 0 dz 2π 0 dθ T (r, t), where L = 2πR is the length of the periodic cylindrical domain, and the plots in Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[16]. More recently, the role of Cantori on anisotropic heat transport in plasmas has been studied in the context of steady state solutions [17] and time dependent solutions in monotonic and reversed shear magnetic configurations [3,4]. The basic idea is that although invariant closed curves (which correspond to flux surfaces in the Hamiltonian description of magnetic fields) present impenetrable transport barriers, regions without such curves (e.g., the region around R 2 ψ ≈ 0.275 in (1/2πL) L 0 dz 2π 0 dθ T (r, t), where L = 2πR is the length of the periodic cylindrical domain, and the plots in Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…[14]. In previous publications, this method was applied to study transport in different magnetic field configurations [2][3][4] but limiting attention to cases in which the heat source was either absent or time independent. Going beyond these previous studies, we consider heat transport in the presence of time modulated sources, and present in this section a re-formulation of the LG method in Fourier space to deal with this problem efficiently.…”
Section: Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…In practical applications, it is ambiguous to distinguish between high and low stochasticity. It is also demonstrated that the RR transport is incompatible with integral (nonlocal) closures [18,19].…”
mentioning
confidence: 99%